Spherical Li4Ti5O12/NiO Composite With Enhanced Capacity and Rate Performance as Anode Material for Lithium-Ion Batteries - Liu, Jiequn; Zhong, Shengkui; Chen, Qingrong; Meng, Luchao; Wang, Qianyi; Liao, Zhijian; Zhou, Jian (Frontiers in Chemistry, 2020)
Compositing with metal oxides is proved to be an efficient strategy to improve electrochemical performance of anode material Li4Ti5O12 for lithium-ion batteries. Herein, spherical Li4Ti5O12/NiO composite powders have been successfully prepared via a spray drying method. X-ray diffraction and high-resolution transmission electron microscopy results demonstrate that crystal structure of the powders is spinel. Scanning electron microscopy results show that NiO uniformly distributes throughout Li4Ti5O12 matrix. It is found that compositing with NiO increases both discharge platform capacity and rate stability of Li4Ti5O12. The as-prepared Li4Ti5O12/NiO (5%) exhibits a high initial discharge capacity of 381.3 mAh g-1 at 0.1 C, and a discharge capacity of 194.7 mAh g-1 at an ultrahigh rate of 20 C.